Experiência do usuário e co-design de produto no desenvolvimento de jogos sérios para o público 50+ - Abrahão, Ana Raquel Ruiz (Universidade Federal de São Carlos, 2022)
Introduction: With the demographic transition and the increase in population aging, one of the great challenges of public policies is prevention in primary care, especially in maintaining quality of life and cognitive performance. In this scenario, digital games show up as a possibility to provide advances in preventive stimuli (motor and cognitive), but at the same time there is still a lack of initiatives aimed at design with the older user. Aging must be faced in a multidimensional way, with desires, interests and needs that go far beyond the possible losses resulting from age. Thus, understanding the experience of using digital cognitive training games by people aged 50 and over, and developing them from the participatory design approach from the beginning of the product conception is a research gap. Adapting to the expectations of older users in order to obtain their validation of digital games as a product is one of the great challenges in the area, in addition to bringing social relevance as an instrument of digital inclusion. Method: This exploratory qualitative study investigated the experience of using digital games by people aged 50 or over, with sampling by spontaneous demand and a participatory approach was divided into two interactions with the user, the first was face-to-face testing the 3 games developed in the previous phase and the second iteration was remote, the re-test of the game that had continued development. Respectively, the first study transcribed and categorized the audios during the interview and interaction with the games, while the second study used the Keep, Lose and Change methodology on the product with the interaction being only via the system. games were guided by the User Centered Development process. Objective: Map the user’s profile and experience and co-design during the development of serious digital games for cognitive training. Results: This study provided a set of design recommendations to guide the development of serious cognitive training games centered on the aging user. Based on the results, it is evident that there is an influence of game design on the motivation and perception of the game's value by the user's profile. Conclusions: For digital products to be more successful in the market, it is more efficient to use procedures that seek the active participation of the user, including them in the design process from the beginning. Digitalization is here to stay and services, products and research need to be updated, especially in healthcare through scalable and accessible technological solutions.
User experience and product co-design in developing serious cognitive training games for 50+
Keywords: Design centrado no usuário; Design de produto; Jogos sérios; Treino cognitivo; User experience; Product design; Serious game; Cognitive training; CIENCIAS DA SAUDE::SAUDE COLETIVA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA